"Safety management system" and Significant Plants of Critical Information Infrastructure. Issue 13 (2019) - Kalashnikov, Andrey; Sakrutina, Ekaterina
Abstract: Increasing the safety always was one of the main priorities for significant plants of critical information infrastructure. Under the conditions of intensive development and putting in operation of information technologies, particular attention is paying to issues of providing the safety. One of the solutions is creating the information and analytical system "Safety management system", which implements monitoring information on the safety on the basis by system regularities. In the paper, important functions of the "Safety management system" are considered in the part of timely identification of threats and vulnerabilities. Putting in operation such systems in the significant plants of critical information infrastructure will increase the engineering plants performance safety.